MENINGKATKAN KECERDASAN INTERPERSONAL DAN KEMAMPUAN KERJASAMA MUATAN IPAS MENGGUNAKAN MODEL BAIMBAI PADA SISWA KELAS IVA SDN TELAGA BIRU 7 BANJARMASIN - Annisa Nur Syifa; Noorhapizah; Akhmad Riandy Agusta; Tika Puspita Widya Rini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The issue addressed in this study concerns the low levels of students interpersonal intelligence and collaboration skills. This condition is attributed to the underdevelopment of communication skills and a lack of active student participation during the learning process. To overcome this issue, the BAIMBAI model was implemented. This study aims to describe and analyze the improvement in students’ interpersonal intelligence and collaboration skills through the application of the BAIMBAI model. A classroom action research (CAR) approach was employed, using both qualitative and quantitative methods over the course of four instructional sessions. The research subjects consisted of 18 fourth-grade students at SDN Telaga Biru 7 Banjarmasin. Data were collected through observations based on indicators of interpersonal intelligence and collaboration ability. The findings revealed a significant increase in students' interpersonal intelligence, from 28% "moderately skilled" to 89% "highly skilled" between the first and fourth sessions. Likewise, collaboration skills improved from 33% to 94% in the same period. These results suggest that implementing the BAIMBAI model in IPAS instruction can effectively enhance students’ interpersonal intelligence and their ability to collaborate.